Pengaruh Online Trust Dan Kualitas Produk Terhadap Minat Beli Ulang Dengan Kepuasan Konsumen Sebagai Variabel Intervening Pada Marketplace Shopee - Sputra, Vito Rizaldi Yuda; Udayana, IBN; Ningrum, Nonik Kusuma (Jurnal Ekonomi Pembangunan, 2023)
This research aims to examine the influence of Online Trust and Product Quality on Repurchase Intentions by using Consumer Satisfaction as an intervening variable on Shopee Marketplace. This research uses a quantitative type of research, with a sampling technique using purposive sampling with non-probability sampling. So, this research took a sample of 120 Shopee users. This research uses primary data by distributing questionnaires in the form of closed and open questions given to respondents via the internet. The data was analyzed using SPSS 26.0 and a support application, namely Microsoft Excel 2019. From the research conducted, it is found that Online Trust did not have a positive and significant effect on Repurchase Intention on Shopee marketplace, Product Quality had a positive and significant effect on Purchase Intention Again on Shopee marketplace, Online Trust has a positive but not significant influence on Consumer Satisfaction on Shopee marketplace on the Shopee marketplace, Product Quality has a positive and significant influence on Consumer Satisfaction on Shopee marketplace, Consumer Satisfaction has a positive and significant influence on Repurchase Intention on Shopee marketplace.